Three dimensional modeling using close range photogrametry for historical artifact - H., Nurul Hafizah (2008)
Nowadays, historical artifacts are very valuable to our country. Most museum in Malaysia keep the high value historical artifacts in two dimensional (2D) recorded documentation and cannot give the specific measurements for reconstruction or research purposes. The main objectives of this research are to record and develop the high quality three dimensional images of historical artifact for data documentation so that, the data will be easy to access either for the reliability, accuracy, precision and ensure the originality of the shapes and textures for reconstruction purposes. The implementation of this research is using two techniques which are photograph and laser scanner. This research will focus on the preliminary stage of data recording and processing, digital reconstructions and visualization of artifacts.